“Efecto de 4 meidos de cultivo y 3 dosis de thidiazuron en la induccion de embriogénesis somática en mauritia flexuosa, en iquitos-Perú - Vásquez Briones, Ivone (2009)
In this research, the subject was the establishment of one culture media for the induction of somatic embryogenesis from zygotic embryos of immature fruits of aguaje (Maturitia flexuosa L.). Two treatments of disinfection were tested, the first one with no previous fungicida aplication to the seeds, and the second one with a previous fungicida aplication, the additional disinfection was done with a 0,5% Sodium hypochlorite solution + 5 mUL of Tween for a 10 minutes period, and was later rinsed with sterile di.stillated water. In order to estbablish the culture media for the induction of somatic embryogenesis, 4 culture media were tested, added with 50 mg/L of 2,4-D y 4 levels of TDZ (O; 0,001; 0,003 y 0,005 mg/l). Wlth this observation, the effect of different concentrations of dychlorophenoxyacetic acid and thidiazuron over the used explants was studied, additionally, the forrnation of the different stages of somatic embñogénesis was evaluated. the process of friable and embryogenic callus forrnation were studied. The contamination percentage decreased significally with the application of Vitavax (0,5 mg/l) 24 hours prior to the seed, and the aplied disinfection treatment was a 0,5 % sodium hypochlorite solution plus 5 ml/l of Tween for a 10 minutes period. The most appropiate mineral concentration for the induction of somatic embryos is the Murahige & Skoog culture media, at total concentration + 50 mg/L of 2,4-D + O mg/L of TDZ. In the treatments T1, T2, T5 and T9, it was observed the presence of embryogenic callus with pro-embyo globural structures within 25 days of incubation.